1901 N.D. Laws 133-34 - (:unkn) unknown (My University, 1901)
Ch. 70, § 1: Every person who either . . . 5. Shall at any time catch or kill any of the birds permitted to be killed by this act at any time in any other manner than by shooting them with a gun held at the shoulder by a person discharging the same; or 6. Shall at any time set, lay or prepare any traps, snare, net, bird line, medicated, drugged or poisoned food or grain, or swivel gun or any contrivance or device whatever with intent to catch, take, or kill any of the birds in this act mentioned, whether the same are caught or not . . . is guilty of a misdemeanor, and upon conviction thereof before any justice of the peace of the county, is punishable by a fine of not exceeding ten dollars . . . for each violation of subdivisions 5 or 6 of this section[.]
Keywords: HUNTING REGULATION